«BRAIN DRAIN» FROM RUSSIA AS A POLITICAL-MANAGEMENT PROBLEM - M. V. Kharkevich (Vestnik MGIMO-Universiteta)
The article analyses the state of the art and the prospects of the Russian political science in terms of scientific communication. Political science develops through discussion on key problems of its subject matter: political power, legitimacy, justice, political regimes, etc. The quality of the discussion shapes the development of political science. The basic medium of the discussion remains an article in a scientific journal. Editorial policy of the leading journals is a key instrument for shaping the discussion and defining its norms and standards. There are few challenges for the Russian political science with respect to the development of a dialogue among its authors and scientific schools. First, it still has a form of a monologue rather than dialogue. There are a number of attempts to establish a dialogue with the leading foreign authors and a deficit of discussion among Russian political scientists. Second, double blind peer review still remains a rear practice. It is the only means for ensuring the high quality of scientific communication. Third, the quality of the discussion directly depends upon the differentiation of political science in the form of scientific schools. The Russian political science has a low degree of school differentiation. And the few schools that did manage to get established evade a dialogue on constitutive questions on theory and practice of political science. The author suggests that coordination of the leading journals’ editorial policy through different forms of institutional interactions including the Russian Political Science Association and the Russian International Studies Association might be an effective tool to encourage the discussion in the Russian political science and dialogue among its schools.